Enteropathogenic microorganisms in children - Tandukar, S; Sherchand, O; Singh, A; Sherchand, JB (Journal of Institute of Medicine Nepal, 2009)
Introduction: Diarrhoeal disease is a leading cause of mortality and morbidity in the developing world. It is one of the most important causes of death in childhood and is still a considerable public health problem in developing countries especially among less than five years old. Materials and Methods: Stool samples from children attending both ORT centre and OPD of Kanti Children's Hospital below 10 years of age were collected and simultaneously data on predisposing factors associated with gastroenteritis along with acute diarrhoea were collected according to the questionnaire designated. The collected stool samples were brought immediately to the laboratory. Upon arrival the stool samples were processed according to the standard laboratory methods. Result: The distribution of enteropathogens showed that rotavirus was found highest constituting 27% of the total cases. Among parasites, protozoan (12.2%) dominated over helminthes (3.0%). Among the protozoa, Entamoeba. histolytica (7.0%) was major causative agent of dysentery followed by Giardia lambia (3.8%), Cyclospora cayetanensis (1.2%), and Entamoeba coli (0.3%). Among the helminthes, Ascaris lumbricoices was the major pathogen constituting 1.3% followed by Trichuris trichiura (0.8%), Hookworm (0.5%) and Hymenolepis nana (0.3%) of the total cases. Similarly, among bacteria Shigella spp. was highest of the total cases. Shigella dysenteriae in 2.0% (12 out of total 607); followed by Shigella flexneri in 1.0% and Shigella boydii in 0.3%. In case of Vibrio cholera it constitutes about 2.0% and Salmonella spp. in 1.3% of total cases. The study shows that the prevalence of Salmonella Paratyphi A in 0.3% (2 out of 607) followed by Salmonella Paratyphi B in 0.3% and Salmonella Typhi in 0.6%. Conclusion: It can be concluded that lots of enteropathogens were involved in children diarrhoea. Among them rotavirus were predominant followed by parasites and bacteria. Children under 2 years were more affected age groups. Key words: Diarrhoea, Enteropathogens, Rotavirus, Bacteria and Parasites The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, December, 2008; 30:3 17-22